Pengelolaan Surat Maya (SURYA) Dinas Koperasi, Usaha Kecil dan Menengah, Perindustrian dan Perdagangan Kabupaten Sragen - Prasetyo, Muhammad; Lestari, Yuni (Universitas Negeri Surabaya, 2023)
The purpose of this study was to describe and find out about the management of SURYA at DISKUMINDAG, Sragen Regency, which has not been running optimally due to incoming mail notifications on the SURYA application that did not appear which resulted in delays in the distribution of letter delivery to departments or official employees and there is no depreciation feature on the SURYA application which causes the last 5 years of archives to be stored and piled up. The method used by the author in this study is to use a descriptive qualitative research method. The results of observations in the field carried out by the author Management and distribution are the stages of incoming and outgoing letters being processed such as entering the date of the letter, subject matter, letter, and author of the letter then the letters that have been managed will then be distributed to fields and outside services. Use is the subject matter stage of incoming and outgoing letters which will be carried out by the service. Maintenance is a step that is carried out by storing incoming and outgoing letters into archives on the SURYA application, the problem with maintenance is that maintenance is carried out every 6 months for the short term and once every 2 years for the long term. Depreciation is the stage for shrinking archives that have been stored for more than 5 years. Keywords: Archives, Management of Virtual Mail Applications (SURYA), Wallace